Pengembangan Modul Pembelajaran Berbasis Model Pembelajaran Kooperatif Tipe AIR - Nur, Fitriani; Amalia Rasyid, A. Fitrah; Sriyanti, A.; Tayeb, Thamrin (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2025)
Education is a basic human need that must be realized through effective learning methods. The purpose of this research is to develop a learning module in number theory course based on AIR (Auditory, Intellectually, and Repetition) cooperative learning model, which meets the standards of validity, practicality, and effectiveness. This research is a type of development research (Research and Development, R&D) using the ADDIE model. Data were collected through questionnaires, observations, and learning outcomes tests. The subjects of this study were 27 students of Mathematics Education Study Program of UIN Alauddin Makassar. The instruments used include module validation sheet, module implementation observation sheet, student response questionnaire, lecturer response questionnaire, student activity sheet, lecturer observation sheet in managing learning, and learning outcomes test. The data were analyzed based on the validity, practicality, and effectiveness of the module. The results showed that the developed learning module has met the criteria of validity, practicality, and effectiveness. Thus, the learning module based on AIR type cooperative learning model is feasible to be used in learning number theory courses.